Praktek Composting sebagai Pengenalan Konsep Ekonomi Sirkular untuk Siswa Sekolah Dasar di SDN Pamarayan 1 - Yusina Fadla Ilmi; Budi Mulyati; Fitri Nurlaili; Khristina Sri Prihatin; Dede Rohadi Fajri (Universitas Serang Raya, 2024)
Circular economy or sustainable economy is one of the pillars in Indonesia's vision for 2045. Dissemination of the circular economy to society needs to be carried out massively and intensively in various sectors. However, there are not many activities or learning related to the circular economy for elementary school. This activity aimed to provide education to elementary school students at SDN Pamarayan 1 through the practice of composting which is one part of utilizing organic waste. This service activity is carried out in a classical class using interactive and practical learning, so beside providing material on waste management, it is also followed by the practice of making compost.